Law, Economy and Society. Essays in the History of English Law 1750 -1914, ed. G. R. Rubin-D. Sugerman, 1984 - Czarnota, Adam (Czasopismo Prawno-Historyczne, 1989)
Recenzja: Law, Economy and Society. Essays in the History of English Law 1750- 1914 (ed. G. R. Rubin i D. Suge rm an), Professional Books, Abingdon 1984